Z XIX-wiecznej gwarowej praktyki leksykograficznej (na podstawie Słowniczka wyrazów ludowych we wsi Jaksicach Zygmunta Wasilewskiego) - Cygan, Stanisław (Gwary Dziś, 2022)
The article revolves around the lexicographic practice of Zygmunt Wasilewski, a lawyer, politician, journalist, literary critic in reference to his 19th-century regional glossary from the village of Jaksice, Pińczów county (central-northern Małopolska). In characterizing this set of words (212 entry words), I have taken into account the macro- and microstructure of the glossary. The lexical material contained in The Glossary is primarily a source of knowledge of the sub-dialects of Kielce Region in research into Polish sub-dialects in general. It also gives insight into the technique of this unqualified lexicographer, a folk culture enthusiast in his youth.